Iron record associated with sandstorms in a central Asian shallow ice core spanning 1956–2004. (15th April 2019) - Du, Zhiheng; Xiao, Cunde; Zhang, Wangbin; Handley, Mike J.; Mayewski, Paul A.; Liu, Yaping; Li, Xiangying
Abstract: The metal elements in alpine ice can provide historical information about natural mineral dust and anthropogenic pollutant emissions. To determine how the Fe concentration and flux variations relate to natural sandstorms and anthropogenic emissions from 1956 to 2004 A.D., Fe, Al, Pb and other element records were measured in a shallow ice core from the Miaoergou Glacier in East Tienshan, central Asia. The results indicate that the dissolved Fe (DFe) and total dissolved Fe (TDFe) peaks are well correlated with sandstorms from the surrounding Taklamakan Desert since at least 1956 A.D. The concentrations and fluxes of Pb show continuously increasing trends since 1995 A.D. due to the accelerating progress of the industrial revolution in China during this period, while the DFe and TDFe concentrations and the fractional Fe solubility exhibit no significant variations during this period. These results provide an ideal opportunity to investigate the effects of the natural Fe record in an arid region. Graphical abstract: Image 1 Highlights: High-resolution Fe records from 1956 to 2004 were identified in the Miaoergou ice core. The Pb element increased with anthropogenic industrial activities. The fraction of soluble Fe varied with sandstorms from 1956 to 1990s.